PENGARUH MOTIVASI, LINGKUNGAN KERJA, SEMANGAT KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DI BANK MANDIRI TASPEN CABANG KLUNGKUNG - Ni Luh Candra Dewi; Ni Putu Yeni Astiti; I Nyoman Resa Adhika (Program Studi Manajemen Fakultas Ekonomi dan Bisnis UNMAS, 2023)
This study aims to examine and analyze the effect of motivation, work environment, morale, and job satisfaction on employee performance at Bank Mandiri Taspen, Klungkung Branch. This research was conducted at PT. Bank Mandiri Taspen Klungkung Branch, which is located at Jl. Untung Surapati No. 36, Semarapura, Kec. Klungkung, Kab. Klungkung. The population in this study are all permanent employees of PT. Bank Mandiri Taspen Klungkung Branch. Determining the number of samples in this study was by saturated sampling or the census method because the population was less than 100, so the researchers took 100% of the existing population, namely as many as 35 permanent employees of PT. Bank Mandiri Taspen Klungkung Branch. The analytical method used is multiple linear regression analysis. The results showed that motivation had a positive and significant effect on employee performance, work environment had a positive and significant effect on employee performance, morale had a positive and significant effect on employee performance, and job satisfaction had a positive and significant effect on employee performance at Bank Mandiri Taspen Klungkung Branch.